On the Local Profiles of Trees. Issue 2 (11th March 2015) - Bubeck, Sébastien; Linial, Nati
Abstract: We study the local profiles of trees. We show that in contrast with the situation for general graphs, the limit set of k ‐profiles of trees is convex. We initiate a study of the defining inequalities of this convex set. Many challenging problems remain open.